Hearing a point-light talker: An auditory influence on a visual detection task - Kim, J.; Kroos, Christian; Davis, C. (Pion Ltd, 2010)
Parsing of information from the world into objects and events occurs in both the visual and auditory modalities. It has been suggested that visual and auditory scene perceptions involve similar principles of perceptual organisation. We investigated here cross-modal scene perception by determining whether an auditory stimulus could facilitate visual object segregation. Specifically, we examined whether the presentation of matched auditory speech would facilitate the detection of a point-light talking face amid point-light distractors. An adaptive staircase procedure (3-up – 1-down rule) was used to estimate the 79% correct threshold in a two-alternative forced-choice procedure. To determine if different degrees of speech motion would show auditory influence of different sizes, two speech modes were tested (in quiet and Lombard speech). A facilitatory auditory effect on talking-face detection was found; the size of this effect did not differ between the different speech modes.